Frog and toad are friends - Lobel, Arnold (New York : HarperCollins Publishers, 1970)
Five tales recounting the adventures of two best friends--Frog and Toad.
Caldecott Honor
Keywords: Friendship -- Fiction; Frogs -- Fiction; Toads -- Fiction